23Na Magnetic Resonance Imaging of the Lower Leg of Acute Heart Failure Patients during Diuretic Treatment - Hammon, Matthias; Großmann, Susan; Linz, Peter; Kopp, Christoph; Dahlmann, Anke; Garlichs, Christoph; Janka, Rolf Matthias; Luft, Friedrich C.; Uder, Michael; Titze, Jens; Cavallaro, Alexander Josef (PLoS ONE, 2015)
Na+ can be stored in muscle and skin without commensurate water accumulation. The aim of this study was to assess Na+ and H2O in muscle and skin with MRI in acute heart failure patients before and after diuretic treatment and in a healthy cohort.Nine patients (mean age 78 years; range 58-87) and nine age and gender-matched controls were studied. They underwent 23Na/1H-MRI at the calf with a custom-made knee coil. Patients were studied before and after diuretic therapy. 23Na-MRI gray-scale measurements of Na+-phantoms served to quantify Na+-concentrations. A fat-suppressed inversion recovery sequence was used to quantify H2O content.Plasma Na+-levels did not change during therapy. Mean Na+-concentrations in muscle and skin decreased after furosemide therapy (before therapy: 30.7±6.4 and 43.5±14.5 mmol/L; after therapy: 24.2±6.1 and 32.2±12.0 mmol/L; p?0.05 and p?0.01). Water content measurements did not differ significantly before and after furosemide therapy in muscle (p = 0.17) and only tended to be reduced in skin (p = 0.06). Na+-concentrations in calf muscle and skin of patients before and after diuretic therapy were significantly higher than in healthy subjects (18.3±2.5 and 21.1±2.3 mmol/L).23Na-MRI shows accumulation of Na+ in muscle and skin in patients with acute heart failure. Diuretic treatment can mobilize this Na+-deposition; however, contrary to expectations, water and Na+-mobilization are poorly correlated.
EVALuna2:3828

3 Tesla (23)Na Magnetic Resonance Imaging During Acute Kidney Injury - Hammon, Matthias; Großmann, Susan; Linz, Peter; Seuss, Hannes; Hammon, Rebecca; Rosenhauer, Daniela; Janka, Rolf Matthias; Luft, Friedrich C.; Titze, Jens; Uder, Michael; Dahlmann, Anke; Cavallaro, Alexander Josef (Academic Radiology, 2017)
Sodium and proton magnetic resonance imaging ((23)Na/(1)H-MRI) have shown that muscle and skin can store Na(+) without water. In chronic renal failure and in heart failure, Na(+) mobilization occurs, but is variable depending on age, dialysis vintage, and other features. Na(+) storage depots have not been studied in patients with acute kidney injury (AKI).We studied 7 patients with AKI (mean age: 51.7 years; range: 25-84) and 14 age-matched and gender-matched healthy controls. All underwent (23)Na/(1)H-MRI at the calf. Patients were studied before and after acute hemodialysis therapy within 5-6 days. The (23)Na-MRI produced grayscale images containing Na(+) phantoms, which served to quantify Na(+) contents. A fat-suppressed inversion recovery sequence was used to quantify H2O content.Plasma Na(+) levels did not change. Mean Na(+) contents in muscle and skin did not significantly change following four to five cycles of hemodialysis treatment (before therapy: 32.7 ± 6.9 and 44.2 ± 13.5 mmol/L, respectively; after dialysis: 31.7 ± 10.2 and 42.8 ± 11.8 mmol/L, respectively; P > .05). Water content measurements did not differ significantly before and after hemodialysis in muscle and skin (P > .05). Na(+) contents in calf muscle and skin of patients before hemodialysis were significantly higher than in healthy subjects (16.6 ± 2.1 and 17.9 ± 3.2) and remained significantly elevated after hemodialysis.Na(+) in muscle and skin accumulates in patients with AKI and, in contrast to patients receiving chronic hemodialysis and those with acute heart failure, is not mobilized with hemodialysis within 5-6 days.
EVALuna2:14621

3 Tesla (23)Na magnetic resonance imaging during aerobic and anaerobic exercise - Hammon, Matthias; Großmann, Susan; Linz, Peter; Kopp, Christoph; Dahlmann, Anke; Janka, Rolf Matthias; Uder, Michael; Titze, Jens; Cavallaro, Alexander Josef (Academic Radiology, 2015)
The aim of the work described here was to determine the feasibility of monitoring Na(+) concentration and distribution in muscle/skin during aerobic/anaerobic exercise with (23)Na magnetic resonance imaging (MRI).The Na(+) concentration and water content of muscle/skin of the left lower leg of six healthy subjects (mean age, 26 years; range, 22-30 years; three men and three women) were assessed before and after aerobic/anaerobic cycle ergometry and during recovery with 3-T (23)Na/(1)H MRI. (23)Na MRI was performed with a custom-made knee coil. A gradient echo sequence with an acquisition time of 3.25 minutes, echo time of 2.07 ms, repetition time of 100 ms, and spatial resolution of 3 × 3 × 30 mm(3) was applied. Phantoms with increasing sodium concentration served for quantification via linear extrapolation. Blood values were determined by blood gas analysis.The concentration of Na(+) significantly increased during anaerobic exercise in all muscle compartments except the medial gastrocnemius muscle, whereas no significant change was observed in most muscle compartments during aerobic exercise (only the soleus muscle exhibited a significant increase in Na(+) concentration during aerobic exercise: 1.6 ± 1.5 mmol/kg, 4.5%, P = .046). During anaerobic exercise, the mean Na(+) concentration of the triceps surae and the whole leg increased by 9.0% (3.1 ± 2.1 mmol/kg, P = .016) and 6.5% (2.2 ± 1.3 mmol/kg, P < .01). MRI revealed a water-independent increase in Na(+) concentration in most muscle compartments during anaerobic exercise. Na(+) concentration significantly decreased during recovery after anaerobic and aerobic exercise in all muscle compartments except the soleus. The Na(+) concentration of the skin did not significantly change during anaerobic/aerobic exercise.Sodium(23) MRI allows reliable and noninvasive visualization and quantification of Na(+) concentration and distribution in muscle and skin during exercise. (23)Na MRI can be used to gain new insights into Na(+) homeostasis, presumably leading to better comprehension of pathophysiology.
EVALuna2:3827